Juridical Review of Legal Protection for Child Perpetrators of Theft in the Juvenile Criminal Justice System in Indonesia - Nurul ‘Aini; Sumarno Sumarno; Suci Ramadani (Journal of Research in Social Science and Humanities, 2025)
Protection for children in conflict with the law is a crucial part of Indonesian criminal law, as regulated in the Juvenile Criminal Justice System (SPPA). Children who commit crimes, including theft, cannot be held legally accountable on an equal basis with adults. Therefore, the SPPA prioritizes the implementation of restorative justice through various mechanisms aimed at restoring the relationship between child perpetrators, victims, and the community. This study aims to analyze the criminal law provisions for child theft perpetrators based on the SPPA and examine the obstacles and efforts to enforce the law by law enforcement officials. The research method used is normative juridical by examining relevant regulations and literature. The results show that, normatively, the SPPA provides adequate legal protection for children, such as setting the age of criminal responsibility, humane treatment, and out-of-court settlements. However, in practice, various obstacles remain, including limited understanding among officials, inadequate supporting facilities, weak coordination between institutions, and a repressive public mindset. Improvement efforts are carried out through increasing the capacity of officials, coordination, providing child-friendly facilities, and promoting restorative approaches